Effect of Magnetic Field Distribution on tile Performance of the Electromagnetic Flowmeter in Partially-Filled Pipes - Najem, S. F.; Rashack, Qals A.; Ismael, Muneer A. (Basrah Journal for Engineering Sciences, 2009)
Electromagnetic flowmeters have proven their merit in· measuring the flow rate of conducting liquids in fully-filled pipes. In contrast with the most of the published works about the electromagnetic flowmetcr, the attentions were focused in this work into the use of these devices in partially-filled pipes. In this application these devices suffer from the problem of different outputs with different liquid level for the same flow rale. We studied whether the process of changing the distribution of the magnetic field through the measuring section improves lhe tlo,~rneter performance against this drawback or not. An adaptive numerical mesh was used in predicting the flow induced signal and its response to the liquid level. The induced signal was assumed to he picked up by a pair of point electrodes tested for different angular positions. The results showed that the performance of the electromagnetic flowmeter in partially-filled pipes could be appreciably improved by making the magnetic field progtessively decreases from top to the bottom of the flowmeter. When the lower magnet coil is excited by a current one-half lower than the upper coil together with two point electrodes placed at 22° below the flowmetcr horizontal centerline, the flowmeter performance offer more stable sensitivity.